Technology of nitriding in a glow discharge of steels for cutting set of shredding meat machines. - Стечишин, М.С.; Олександренко, В.П.; Лук’янюк, М.В.; Люховець, В.В.; Лук’янюк, М.М. (Problems of Tribology, 2017)
The influence of nitriding in a glow discharge modes on phase and structural composition of nitrided layer, the thickness of its compound and diffusion zones and distribution of microhardness in nitrided layer were investigated. Con-ducted laboratory and production tests showed the increase of cutting set of shredding meat machines’ durability in 4 - 10 times. Key words: durability, nitriding in a glow discharge, knives of cutters and choppers, nitride and diffusion zones.